A Direct Sulfation Process of a Marine Polysaccharide in Ionic Liquid. (19th May 2015) - Chopin, Nathalie; Sinquin, Corinne; Ratiskol, Jacqueline; Zykwinska, Agata; Weiss, Pierre; Cérantola, Stéphane; Le Bideau, Jean; Colliec-Jouault, Sylvia
Abstract : GY785 is an exopolysaccharide produced by a mesophilic bacterial strain Alteromonas infernus discovered in the deep-sea hydrothermal vents. GY785 highly sulfated derivative (GY785 DRS) was previously demonstrated to be a promising molecule driving the efficient mesenchymal stem cell chondrogenesis for cartilage repair. This glycosaminoglycan- (GAG-) like compound was modified in a classical solvent ( N, N ′-dimethylformamide). However, the use of classical solvents limits the polysaccharide solubility and causes the backbone degradation. In the present study, a one-step efficient sulfation process devoid of side effects (e.g., polysaccharide depolymerization and/or degradation) was developed to produce GAG-like derivatives. The sulfation of GY785 derivative (GY785 DR) was carried out using ionic liquid as a reaction medium. The successful sulfation of this anionic and highly branched heteropolysaccharide performed in ionic liquid would facilitate the production of new molecules of high specificity for biological targets such as tissue engineering or regenerative medicine.